Surfactant Protein A Inhibits Human Rhinovirus C Binding and Infection of Airway Epithelial Cells from Pediatric Asthma - Sasipa Tanyaratsrisakul; Yury A. Bochkov; Vanessa White; Heejung Lee; Jessica Loeffler; Jamie Everman; Allison M. Schiltz; Kristy L. Freeman; Katharine L. Hamlington; Elizabeth A. Secor; Nathan D. Jackson; Hong Wei Chu; et al. (Viruses)
Rhinovirus C (RV-C) infection can trigger asthma exacerbations in children and adults, and RV-C-induced wheezing illnesses in preschool children correlate with the development of childhood asthma. Surfactant protein A (SP-A) plays a critical role in regulating pulmonary innate immunity by binding to numerous respiratory pathogens. Mature SP-A consists of multiple isoforms that form the hetero-oligomers of SP-A1 and SP-A2, organized in 18-mers. In this report, we examined the efficacy of SP-A to antagonize RV-C infection using the wild-type (RV-C15) and reporter-expressing (RV-C15-GFP) viruses in differentiated nasal epithelial cells (NECs) from asthmatic and non-asthmatic children. We also determined the antiviral mechanism of action of SP-A on RV-C15 infection. The native SP-A was purified from alveolar proteinosis patients. The recombinant (r) SP-A1 and SP-A2 variants were expressed in FreeStyle™ 293-F cells. SP-A reduced the fluorescent focus-forming units (FFUs) after RV-C15-GFP infection of NECs by 99%. Both simultaneous and 4 h post-infection treatment with SP-A inhibited RV-C15 and RV-C15-GFP viral RNA load by 97%. In addition, the antiviral genes and chemokines (IFN-λ, IRF-7, MDA-5, and CXLC11) were not induced in the infected NECs due to the inhibition of RV-C propagation by SP-A. Furthermore, SP-A bound strongly to RV-C15 in a dose- and Ca2+-dependent manner, and this interaction inhibited RV-C15 binding to NECs. In contrast, rSP-A1 did not bind to solid-phase RV-C15, whereas the rSP-A2 variants, [A91, K223] and [P91, Q223], had strong binding affinities to RV-C15, similar to native SP-A. This study demonstrates that SP-A might have potential as an antiviral for RV infection and RV-induced asthma exacerbations.